Panicum virgatum microbial community and soil chemistry responses to conservation agriculture management - Kazarina, Anna (Kansas State University, 2021)
The holobiont concept of plants treats plants with their associated microbiomes that mostly consist of the fungi and bacteria as a single unit. Previous studies have shown the central role of microbiomes for plant health and performance, while also highlighting that the dynamic nature of the microbiomes can be affected by various biotic and abiotic factors that can rapidly change microbiome functionality. In the past two decades, development of novel technologies has substantially advanced research methods used to study plant and microbiome interactions – thus allowing for better identification of factors that shape microbiomes. Although effects of agricultural and production management on the plant, plant microbiomes and plant-associated soils are relatively well understood, effects of practical tools commonly employed in conservation agriculture remain largely unknown. Conservation agriculture management aims to achieve sustainable plant growth and productivity while minimizing active management such as fertilization, tillage, and soil movement. As a result of this lack of active management, conservation agriculture regimes promote the use of practical tools such as variety and planting density choices to achieve sustainable conservation goals The research described in this thesis aims to evaluate effects of conservation agriculture management on bacterial and fungal communities associated with soil and roots of four varieties of the native warm-season perennial grass Panicum virgatum L. (a.k.a. switchgass) initially planted at two different densities and growing under conservation agriculture conditions in southeastern Mississippi. To also assess the temporal dynamics, we repeatedly sampled switchgrass roots and associated soils approximating a log2 time series for a total of six times during one growing season, starting from within a week from the first leaf emergence in early spring to pre-frost in late fall. A small-scale pilot study comparing DNA isolation kits (Phire Plant Direct PCR vs. PowerSoil DNA Isolation kits) confirmed that, although the direct extraction and amplification kits provide a cost-effective and expedient alternative to the more commonly used PowerSoil kits, the direct kits do not produce comparable community views from all plant tissues. Our studies of switchgrass microbiomes highlight that, while bacterial and fungal communities in roots and soils are temporally dynamic and shift compositionally during the growing season, planting densities have no strong overall effect on microbiome richness, diversity, or composition, and that if microbiomes associated with four switchgrass varieties differed among switchgrass varieties, they did so only in the beginning of the growing season. Indicator taxon analyses identified many bacterial and fungal taxa in soil and roots that represent potential variety specific taxa in the early season and temporally dynamic taxa. Similar to the biotic attributes, the soil chemistry was minimally affected by switchgrass variety choice or planting density, although some temporal dynamics were observed. These findings indicate that in the hierarchy of tested factors, seasonal dynamics are the strongest driver of switchgrass microbiomes and soil chemistry. The seasonal dynamics overwhelm the effects of conservation agriculture management choices, as shown here for choice of switchgrass variety and planting density. Notwithstanding and based on our indicator taxon analyses that identified putative plant symbionts and pathogens or soil-inhabiting nitrogen fixing taxa, careful variety choices can potentially facilitate mindful microbiome manipulations to support the sustainable switchgrass productivity.
Keywords: Microbiome; Seasonal dynamics; Switchgrass; DNA extraction tools; Conservation agriculture